STEM-15. CDK5 AND NOTCH SIGNALING CROSSTALK DRIVES SELF-RENEWAL IN GSCs. (5th November 2018) - Mukherjee, Subhas; Lee, Hannah; Broger, Leah; Olson, Cheryl; Brat, Daniel
Abstract: While the connection between stem cell biology, deregulation of self-renewal properties in glioma stem cells and involved signaling pathways which inherent and/or adaptive to tumor cell resistance has long been considered an important area of cancer research, studies on glioma stem cell self-renewal mechanisms has not always been forthcoming. In this regard, the role of atypical Cyclin Dependent Kinase 5 (CDK5) and its pathway in maintaining self-renewal properties has been characterized. CDK5 is a cyclin dependent kinase family member that does not regulate cell cycle directly. CDK5 is highly important for the survival of post-mitotic neurons and its aberrant activation has been instrumental in neurodegenerative diseases. Our research, as well as that of others, has identified CDK5 as a regulator of self-renewal in glioma stem cells (GSCs). In this capacity, the CDK5 directly activates CREB1 transcription factor independent of PKA/cAMP pathway to drive self-renewal. In the current study we have shown that CDK5 signaling is also a regulator of NOTCH1 activation. Notch pathway regulates self-renewal and asymmetric division through activation of Hes1 transcription factor. Notch pathway is also regulated by Numb and TRIM3 in GSCs and interestingly, TRIM3 regulates CDK5 activity. Our study unravels a signaling crosstalk between CDK5 and NOTCH1 in regulating self-renewal of GSCs.